Kesehatan Mental Dalam Islam - Yudha Hafidh Pratama; Ahmad Raihan Anargya; Athila Shofia Rosidah (Pusat riset dan Inovasi Nasional, 2023)
Mental health is a vital aspect of deep human life, and religious views play a crucial role in understanding it. This research aims to explore and understand the relationship between mental health and religious perspectives on individual quality of life. The research method used was a systematic review by searching for articles on Google Scholar using the keywords